Correlation between the Al content and corrosion resistance of TiAlN coatings applied using a PACVD technique. Issue 1 (2nd January 2020) - Elmkhah, H.; Fattah-alhosseini, A.; Babaei, K.; Abdollah-Zadeh, A.; Mahboubi, F.
ABSTRACT: The present study aims to determine the effect of Al on the corrosion resistance of nanostructured TiAlN coatings deposited using a pulsed direct current plasma-assisted chemical vapor deposition (pulsed-DC PACVD) technique. The nanostructured TiAlN coatings were synthesized with three different Al-content values of by distinct precursor's ratio of AlCl3 -to-TiCl4 . The number of AlCl3 -to-TiCl4 precursor ratios was changed from 1 to 3 in order to vary the Al content. FE-SEM, XRD, EPMA and a Knoop micro-hardness tester were used to characterize the coated surfaces of the specimens. Electrochemical corrosion tests were carried out at 25 ± 1°C to investigate the corrosion behavior of the substrate and the TiN and TiAlN nanostructured coatings in 3.5 wt % NaCl solution. The results indicated that the potentiodynamic polarization plots revealed the passive behavior of TiAlN(2) nanostructured coatings that were more improved than the TiN, TiAlN(1) and TiAlN(3) coatings. Moreover, these curves showed that the TiAlN(2) nanostructured coating had an exceptional polarization resistance that was considered much higher than those of the substrate, TiN, TiAlN(1) and TiAlN(3) coatings. Also, the impedance spectroscopy plots showed that the TiAlN (2) coating had an exceptionally high polarization resistance compared to the substrate and other coatings.